Molecular Identification of Two Thioredoxin Genes From Grapholita molesta and Their Function in Resistance to Emamectin Benzoate - Shen, Zhong-Jian; Liu, Yan-Jun; Gao, Xu-Hui; Liu, Xiao-Ming; Zhang, Song-Dou; Li, Zhen; Zhang, Qing-Wen; Liu, Xiao-Xia (Frontiers in Physiology, 2018)
Thioredoxins (Trxs), member of the thioredoxin system, play crucial roles in maintaining intracellular redox homeostasis and protecting organisms against oxidative stress. In this study, we cloned and characterized two genes, GmTrx2 and GmTrx-like1, from Grapholita molesta. Sequence analysis showed that GmTrx2 and GmTrx-like1 had highly conserved active site CGPC and CXXC motif, respectively, and shared high sequence identity with selected insect species. qRT-PCR results revealed that GmTrx2 was mainly detected at first instar, whereas GmTrx-like1 was highly concentrated at prepupa day. The transcripts of GmTrx2 and GmTrx-like1 were both highly expressed in the head and salivary glands. The expression levels of GmTrx2 and GmTrx-like1 were induced by low or high temperature, E. coli, M. anisopliae, H2O2, and pesticides (emamectin benzoate). We further detected interference efficiency of GmTrx2 and GmTrx-like1 in G. molesta larvae and found that peroxidase capacity, hydrogen peroxide content, and ascorbate content all increased after knockdown of GmTrx2 or GmTrx-like1. Furthermore, the hydrogen peroxide concentration was increased by emamectin benzoate and the sensitivity for larvae to emamectin benzoate was improved after GmTrx2 or GmTrx-like1 was silenced. Our results indicated that GmTrx2 and GmTrx-like1 played vital roles in protecting G. molesta against oxidative damage and also provided the theoretical basis for understanding of the antioxidant defense mechanisms of thioredoxin system in insects.